NEUROPATHIC COMPONENT OF PAIN IN RHEUMATOID ARTHRITIS AND TREATMENT METHODS - Mirzayev Ozod Voxidovich; Norbo'toyev Olimjon Mustafaqul o'g'li (Scholars Digest Publishing, 2024)
The article discusses the pathogenesis of pain in rheumatoid arthritis (RA), presenting a large body of literature and findings from our own research on the prevalence and significance of polyneuropathy in the development of peripheral neuropathic pain. In RA, peripheral nervous system damage—such as sensory or sensorimotor axonal neuropathy, demyelinating polyneuropathy, and myelopathy—has been documented. Joint deformities, limitations in active and passive movements, and muscle atrophy make it challenging to identify the exact cause of paresis, whether it stems from joint pathology or peripheral nerve damage. Comprehensive treatment of the neuropathic pain component in RA includes nonsteroidal anti-inflammatory drugs, glucocorticosteroids, biologic therapies targeting the underlying disease, and centrally acting medications. B vitamins play an essential role in restoring affected neurons, regenerating peripheral nerves, and aiding myelin sheath synthesis, offering both regenerative and analgesic effects.
Keywords: rheumatoid arthritis, polyneuropathy, B vitamins, pain syndrome.